'Both are equal, which is awesome': exploring gendered discourses of Canadian summer camp experiences. Issue 3 (27th May 2022) - Baker, Mandi; Hannant-Minchel, John
ABSTRACT: This study discusses gendered discourses of summer residential camp experiences and, in particular, the gendered roles performed by camp counsellors. By drawing on feminist poststructuralist concepts, this article considers how gender power-relations operate and how camp counsellors perform gender within camps. We start by considering the history of gender in early camp movements and recent research literature on camps. Interview participants revealed the iteration and reiteration of stereotypic gender norms within camp contexts. The findings suggest that participants found both empowerment and challenge in the assumed genderlessness, or gender neutrality, of camp experiences. Findings also suggest that women counsellors are assumed to do disproportionate amount of care work. The article concludes by considering opportunities for positive youth development when gendered norms are critically considered, resisted and/or transformed within camp contexts.